FACTORS AFFECTING VALUE ADDED TAX REVENUE - Egidijus Bikas; Emile Andruskaite (European Scientific Journal, ESJ, 2013)
This article examines the concept of value added tax, the notion of the tax, the EU directives governing the tax rate base as well as the change of standard rate in European Union countries. The paper also analyses the relationship between the VAT revenue and macroeconomic indicators: gross domestic product, gross domestic product per capita, consumption expenditure, household consumption expenditure, government consumption expenditure, export, import and unemployment in the country in an attempt to construct a model that describes the significance of VAT revenue collected. The article aims to analyse the key factors influencing value-added tax collection in the European Union countries.